2 A rare cause of stroke in young: moyamoya disease. Issue 1132 (22nd January 2020) - Ali, Asem; Abbas, Munzar; Saeed, Umer
Abstract: Background and aims: Moyamoya disease is a rare chronic progressive cerebrovascular disease characterised by bilateral stenosis or occlusion of arteries around circle of Willis with prominent collateral circulation. The term moyamoya (Japanese for 'puff of smoke') refers to the appearance on angiography of abnormal vascular collateral networks that develop adjacent to the stenotic vessels. Moyamoya disease was first described in Japan by Takeuchi and Shimizu in 1957. 1 The prevalence and incidence of the disorder there has been reported to be 3.16 cases and 0.35 cases per 100 000 people, respectively. The incidence of moyamoya disease is highest in Japan. 2 Moyamoya syndrome has now been observed throughout the world with increasing detection of this disease in American and European populations. 3 4 Methods: 32 years old gentleman with background of Rheumatoid arthritis (In remission) and asthma presented to hospital with confusion and word finding difficulty. Results: Systemic examination was unremarkable except patient mentioned that he had difficulty in texting on his mobile phone. Blood tests showed raised inflammatory markers. Patient was treated on lines of meningoencephalitis. CT brain showed hypodensity in left temporal, parietal and occipital lobe. MRI brain with contrast showed confirmed these changes to be acute infarcts along with post contrast meningeal enhancement. CSF results came back normal including viral PCR.Patient referred to neurology who advised to continue treating as viral encephalitis. Vasculitic screen weakly positive P-ANCA. Stroke team was involved who organised MRA which showed generalised narrowing of left carotid siphon and left middle cerebral artery and its branches. It also showed loss of definition of M1 segment of right MCA and its branches. Changes initially though to be secondary to vasculitis and patient started on steroids. Patient seen by rheumatology team and possibility of vasculitis was ruled out. Neuroimaging was discussed in neuroradiology MDT after doing DSA and outcome was that changes on brain imaging were suggestive of moyamoya disease with extensive disease bilaterally with more on left side. Patient was seen in neurosurgery clinic and offered revascularisation surgery which patient refused. Patient is under surveillance by neurosurgical team. Conclusion: Moyamoya is a rare cause of stroke which is diagnosed on basis of clinical and radiographic findings and patients can be offered revascularisation surgery which is the only recommended treatment.